A stranger thing? Sweden as the upside down of multilevel trust. Issue 1 (2nd January 2021) - Erlingsson, Gissur Ó.
ABSTRACT: As a rule, citizens appreciate local more than central government. This paper proposes a new research agenda for multilevel trust studies by arguing that it is premature to believe that citizen's proximity to officials by definition trumps distance. As in country-comparative studies, close attention needs to be paid to institutional quality in analyses of multilevel trust. To put this argument to work, a closer investigation of Sweden is conducted. Tracking three indicators of trust, with time-series stretching over two decades, Sweden turns out to be a curious outlier from the international pattern: Swedes trust their local government less than the state. To make this observation intelligible – while simultaneously aiming to contribute to a more nuanced theoretical understanding of multilevel trust – the mix of three features is identified for bringing this circumstance about: (1) the principal role Swedish municipalities have successively been given in implementing core welfare state assignments; (2) that several of the municipalities' assignments are susceptible to corruption; and (3) that the increase in municipal responsibilities has neither been accompanied with institutions that guarantee accountability of politicians nor the impartiality of local bureaucracies.